El ADN: un tsunami genético que arrasó con el formalismo procesal. El nuevo proceso de filiación, en el nombre del padre - Varsi-Rospigliosi, Enrique (2005)
This article highlights the importance that the paternal attribution has had historically. The autor makes a comment on the Peruvian law 28457 of 8 January 2005 where a new extraordinary process to investigate the extramarital paternity is establisehd.